Musical Vocabularies : creating a framework for meaningful intercultural musical dialogue - Beerten Sapion, Oscar (Taideyliopiston Sibelius-Akatemia, 2023)
In this arts-based research I draw on the approaches of autoethnography and artistic research to uncover findings emerging from my artistic and pedagogical navigation through traditional and contemporary folk and global musics. I explore the processes of my own interpretations and understandings of music-making in intercultural contexts through composing, co-creating, and interacting with musicians from different musical and cultural backgrounds. The title of musical vocabularies refers to the process of gathering and understanding musical aesthetics from diverse and unfamiliar musics as a non-native, and how to integrate and transmit these elements artistically and ethically in my performing and teaching practices. Through exploring musical dialogues and collaborations in this research, I discover different ways of music-making and music-thinking, which involve a variety of pedagogical methods and perspectives. In the first sections of this work, I discuss my positionality by briefly unfolding my artistic and educational background, as well as unpack the core methods applied in this arts-based research. On the basis of three selected artistic case studies, I explore new and unfamiliar musical cultures together with their related pedagogical approaches and thinking. I unfold the working methods used and discuss the compositional processes, which involve co-creating and interacting in an intercultural environment, resulting in three main artistic outcomes, including a duo with a musician from the Faroe Islands, collaborations with musicians in Hungary, and an intercultural trio formed for my master’s concert. Through these case studies, I explore the artistic possibilities of intercultural music-making and how hands-on experience can be translated to teaching practice, suggesting a framework for meaningful intercultural musical dialogue. Key findings include that intercultural musical dialogues require multiple ways of music-thinking and pedagogical approaches. Furthermore, immersion into different cultural contexts, including day to day experiences of the culture and hands on collaboration with musicians from inside each culture are essential elements. Finally, I reflect on possible future directions for intercultural musical dialogue and discuss its complexities and current issues.
Keywords: Intercultural music-making, tacit knowledge, embodiment, translation and transmission, autoethnography, traditional music, musical cultures, contemporary folk music, reflexivity; musiikki; taiteellinen tutkimus; musiikkikasvatus; kansanmusiikki; kulttuurienvälinen tutkimus; Glomas